MYTH OF CHORNOBYL IN THE PLOT OF THE PLAY “AT THE BEGINNING AND THE END OF TIME” BY P. ARIE - Pavlova О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The author of the article studies the process of modern myth creation – an exclusion zone – in the play “At the Beginning and the End of Time” by P. Arie. The author reveals modern aspects of Chornobyl man-made disaster reception: the overlapping and interpenetration of archaic and social myths, the correlation of the concept “us”/“them”, the decoding of mental code of the nation in the post-capitalism period.